Hubungan Perilaku Makan dan Status Gizi Anak Usia Prasekolah - Tsamara Alifia Ramadhani; Lailatul Muniroh (Universitas Airlangga, 2023)
Background: The increase of self-autonomy causes preschool age children have varied eating behavior. Eating difficulties in children can be a factor that affect the amount of food.intake and nutritionalistatus in preschool age children. Objectives: Analyzing the correlation.between.eating behavior and the nutritional status of preschool children. Methods: It was an analytic observational study with a cross-sectional design. The samples were 41 students, selected by simple random sampling technique. Data were collected by measuring anthropometrics, filling out the Behavioral Pediatric Feeding Assessment Scale (BPFAS) and Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). The data were analyzed using SPSS v.20.0 software with the Pearson correlation test. Results: There was no significant.correlation between.eating.behavior (Total Frequency Score) and children's nutritional status (p=0.069); eating behavior (Total Problem Score) with children's nutritional status (p=0.201). Conclusions: Eating behavior is not correlated to nutritional status because there are intervening variables that can affect the dependent variable. Even though children are categorized as having abnormal eating behavior, intake of energy sources can be obtained from other than solid food, especially milk so that children can meet their energy and protein needs and affect the z-score of their nutritional status.